ACCOUNTING CONSULTING AS A TOOL OF ENTERPRISE MANAGEMENT - Hnatyshyn Л.; Matskiv Г.; Prokopyshyn О. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2023)
The research outlines the need of enterprises and other business entities for accounting consulting. In the general sense, accounting consulting is identified as a complex of services provided for enterprises and business, a tool of reducing risks related with the enterprise finance. The article considers directions of the accounting consulting of enterprises. It is noted that professional interests of the consulting firms cover the following aspects, namely keeping records and recovery of accounting at enterprises; internal audit; choice of an optimal system of taxation for the following optimization of tax charges; control over settlements with counterparties and staff; control over the legitimacy of the enterprise’s transactions, including financial ones; analysis of the current documents – audit; choice of the accounting software; control over property, personnel, financial flows; methodic and legal support for liquidation, division, merger or opening of affiliates. It is determined that gradual complication of the methods and forms of accounting is the prerequisite for changing the approaches to the enterprise management and processes of accounting and taxation that has forced the demand for chief and staff accountants to continuously enhance their managerial, organizational and methodological practices with innovative knowledge and skills by cooperating with representatives of the accounting consulting firms. The authors of the work provide characteristics of the procedure, stages, methods and results of accounting consulting of enterprises. It is determined that accounting consulting can be considered a tool of enterprise management, because managerial decisions approved according to the results of cooperation of the business entity and an accounting consulting firm can improve efficiency of the operational management that will significantly increase financial efficiency of the enterprise even in the extreme situation and in case of multiple urgent tasks. The researchers have modeled outcomes of the managerial decisions as to optimization of the accounting system and taxation of the enterprise due to the services provided by accounting consulting firms. It is confirmed that efficiency of the accounting and taxation processes depends on the permanent progress of accounting staff and its incorporation into the realities of today’s world that can be achieved due to accounting consulting.